Disclosure of Corporate Social Responsibility Using Gri Standard Guidelines and its Effect on Financial Performance - Yulia Shine; Apriani Dorkas Rambu Atahau (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2023)
This study aims to find out whether CSR disclosure using the GRI Standards guidelines which include general standards (Governance: General Disclosures and Management Approach) as well as specific standards (Economic, Environmental, and Social), as well as company size affect the financial performance of mining companies that in Indonesia. The variables in this study consist of independent variables, namely governance and economics, environment, and social, one dependent variable, namely financial performance, and one control variable, namely company size. This research uses a causal associative quantitative method. The type of data obtained is secondary data with the collection technique using archival documentation in the form of Sustainability and the company's Annual Report. In this study using the panel data regression research model, so in this study using eviews 12 to process the data with the selected model is the Random Effect Model (REM). The results of this study reveal that economic, environmental, and social have a partial effect on financial performance, but governance does not affect financial performance, nor does company size affect the financial performance of mining companies. However, CSR simultaneously influences financial performance.